Production and Testing of Bamboo Composite for Door of a Three-Wheeled Vehicle - Mulugeta Denanto; Ramesh Babu Nallamothu; Deresse Firew; Idiris Ilmi (Journal of Engineering)
Natural fiber reinforced composite material has recently attracted interest due to its low density, low cost, acceptable specific characteristics, ease of separation, improved energy recovery, CO2 neutrality, biodegradability, and renewable nature. The goal of this paper is to design and construct a three-wheeled Bajaj door panel using composite materials reinforced with bamboo fiber. Design, manufacture of the component, and experimental techniques are used to meet the goals given. The bamboo plant is the raw material chosen for this thesis project. The matrix material (polyester resin) and hardener used in this investigation, as well as the woven bamboo fiber strip that has been used as reinforcement, were all obtained from local markets. Bamboo fiber that has been chemically treated with 5% NaOH and 95% purified water is used. Keeping in mind the needs of varied testing conditions and characterization standards, polyester resin and E-glass fibers were simply stirred together by hand for 15 minutes. The mixture was then put into the molds. In three distinct orientations (0°, 90°, and 0/90°), composite samples of bamboo fiber were created. In order for the part to respond to axial loads, shear loads, and side loads, it may need 0°, 45°, and 90° plies, respectively. The paper model’s 0° orientation was chosen in accordance with the findings of the samples’ analysis. Due to the direction of the applied load, it affects the strength design requirements. Based on the findings of the experimental data examination, it was determined that the respective values for tensile, compression, bending, and water absorption were 160 MPa (0°), 2709.2 MPa (90°), 110 N (0/90°), and 4%, respectively. The geometric model of the door panel on the three-wheel Bajaj vehicle’s door was designed. Based on these findings, it is suggested that the new exterior structural car door panel of the three-wheel Bajaj Compact 205 model be made of composite materials made of bamboo fiber reinforced with polyester and having strength of 160 MPa.